2015
DOI: 10.1177/0040517515576329
|View full text |Cite
|
Sign up to set email alerts
|

Study on effects of structural parameters on untwisting performance in pneumatic yarn splicing

Abstract: The internal airflow of an untwisting chamber clearly affects the untwisting performance as determined by the appearance of the untwisted yarn end. This study established a geometric model of an untwisting chamber comprising an intake tube and untwisting tube, and adopted the renormalization-group k-" turbulence model to simulate the airflow patterns inside chamber structures having three varying parameters. These were the chamfer angle of the intake nozzle, rotation angle of the intake nozzle, and eccentric d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Their findings showed that the Spandex © filament angular position is influenced by the important splicing conditions (splice length and duration of water joining) and, by providing the adequate splicing condition adjustments high splice physical performance is given and a particularly good appearance. Wu et al (19) revealed that pneumatic yarn splicing is a complex process concerning the winding of multi-filaments in a spiral airflow field. They indicated that a proper overlapping length is of benefit to achieve enough winding loops at the free-end of the filament to resist the dragging force exerted by axial airflow and obtain a successful splice subsequently.…”
Section: To Cite This Article: Uyanık S 2018 "A Research On Determmentioning
confidence: 99%
“…Their findings showed that the Spandex © filament angular position is influenced by the important splicing conditions (splice length and duration of water joining) and, by providing the adequate splicing condition adjustments high splice physical performance is given and a particularly good appearance. Wu et al (19) revealed that pneumatic yarn splicing is a complex process concerning the winding of multi-filaments in a spiral airflow field. They indicated that a proper overlapping length is of benefit to achieve enough winding loops at the free-end of the filament to resist the dragging force exerted by axial airflow and obtain a successful splice subsequently.…”
Section: To Cite This Article: Uyanık S 2018 "A Research On Determmentioning
confidence: 99%
“…3 In the air splicer of the auto-winder, a swirling airflow is used to untwist, unravel and open up a yarn to prepare for the piecing process. 4 In the JetRing and JetWind processes, swirling airflows are formed in the air-jet nozzle through which the yarn passes to make the yarn hairs wrap around the yarn body. 5,6 Considering the wide and important applications of swirling airflows in engineering fields, progress in studies on swirling flow is being continuously made.…”
mentioning
confidence: 99%
“…3 In the air splicer of the auto-winder, a swirling airflow is used to untwist, unravel and open up a yarn to prepare for the piecing process. 4 In the JetRing and JetWind processes, swirling airflows are formed in the air-jet nozzle through which the yarn passes to make the yarn hairs wrap around the yarn body. 5,6…”
mentioning
confidence: 99%
“…By analyzing the flow field, they discussed the principal of yarn untwisting and their conclusions confirmed the pneumatic splicer maker's suggestions about the principal of yarn untwisting. Wu et al 5 investigated the structural parameters that affect the untwisting stage. They made comparisons between the flow field simulation and experimental data.…”
mentioning
confidence: 99%